Method for improving connection strength of honeycomb sandwich structure composite material insert

By using multi-component hybrid bonding materials and external thread design in honeycomb sandwich composite inlay inserts, combined with conical mounting area and syringe injection technology, the problem of insufficient connection strength of the inlay is solved, significantly improving the bonding strength and service life of the inlay, ensuring aviation safety.

CN119704750APending Publication Date: 2025-03-28CHINESE PEOPLES LIBERATION ARMY UNIT 61255

Patent Information

Application Number
CN202411914236.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The connection strength of the existing honeycomb sandwich composite inlays is insufficient, which causes the inlays to loosen or fall off under the vibration load of the fuselage during flight and the torque load during repeated disassembly and assembly, causing safety hazards.

Method used

A multi-component hybrid bonding material, including nanosilicon dioxide and short glass fiber wire as reinforcements, is designed in combination with external threaded inserts and conical mounting area, and the bonding material is injected through a syringe to improve the bonding strength between the insert and the composite material parent body.

Benefits of technology

It significantly improves the connection strength of the inlay, reduces the risk of loosening and falling off, extends the service life of honeycomb sandwich composite materials, and meets the safety requirements in the aviation field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119704750A_ABST
    Figure CN119704750A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the connection strength of a honeycomb sandwich structure composite material insert, and the method comprises the following steps: adding a reinforcement into a curing agent, uniformly stirring, then adding into epoxy resin-based glue, and uniformly mixing to prepare a multi-component mixed binding material; wherein the reinforcements are nano silicon dioxide and short glass fiber filaments; a conical mounting area is formed in a honeycomb sandwich structure composite material matrix, an insert provided with an internal thread and an external thread is arranged in the center of the mounting area to be fixed, and the periphery of the insert is filled with a multi-component mixed binding material till the mounting area is completely filled with the multi-component mixed binding material; and then curing is carried out, and installation is completed. According to the method, the technical problems that an existing insert is insufficient in mounting bonding strength and prone to loosening and failure in later use can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bonding composite material inlays, and in particular relates to a method for improving the connection strength of composite material inlays with a honeycomb sandwich structure. Background Art

[0002] Honeycomb sandwich structure composite materials have the advantages of light weight, high strength and stiffness, energy absorption, and sound insulation, and are widely used in the aerospace field. Honeycomb sandwich structure composite materials are generally composed of upper and lower panels, honeycomb core materials, and adhesive layers, and have poor ability to transfer concentrated loads. However, since the honeycomb sandwich structure is inevitably transferred when it is connected to other parts and equipment is installed, it is necessary to reasonably design the connection parts of the honeycomb sandwich structure. The commonly used method is to use various forms of metal inlays for local reinforcement, so that a detachable connection structure is formed between the honeycomb sandwich structure and other structural parts or instruments and equipment to diffuse the concentrated load generated by the connection. Therefore, the connection strength of the inlay directly affects the reliability and fatigue life of the honeycomb sandwich structure composite material, and is often the key link of the entire honeycomb sandwich structure.

[0003] The inlays of honeycomb sandwich composite materials are subject to the vibration load of the fuselage during flight and the torque load during repeated disassembly and assembly. In addition, the natural aging of the epoxy resin causes performance degradation. When the connection strength with the surrounding honeycomb sandwich structure is not strong enough to support the working load, damage will occur in the inlay installation area, causing the inlay to loosen or even fall off.

[0004] The existing aviation composite repair manual chooses to use epoxy resin plus hollow glass microspheres for filling and bonding when solving the problem of failed inlay installation. However, due to the large particle size of hollow glass microspheres (20~70μm) and the lack of fiber reinforcement, there are many pores in the epoxy resin glue, resulting in insufficient bonding strength, and subsequent secondary or even multiple connection failures, which brings serious safety hazards to the use of honeycomb sandwich structure composite materials. For example, due to the failure of the installation of the main reducer fairing inlay of a certain type of helicopter, the tightening torque was lost, and the steel gasket slid into the turboshaft engine along the gap of the engine inlet filter, causing multiple blades to be damaged. The engine had to be returned to the factory for repair. Summary of the invention

[0005] In order to overcome the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a method for improving the connection strength of honeycomb sandwich structure composite material inlays, which can solve the technical problems of insufficient installation bonding strength of existing inlays and easy loosening and failure in later use.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention provides a method for improving the connection strength of a composite material inlay of a honeycomb sandwich structure, comprising the following steps: The reinforcement is added into the curing agent and stirred evenly, and then added into the epoxy resin base glue and mixed evenly to prepare a multi-component mixed bonding material; wherein the reinforcement is nano-silicon dioxide and short glass fiber filaments; A conical installation area is opened in a honeycomb sandwich structure composite material matrix, an inlay with internal and external threads is placed and fixed at the center of the installation area, and a multi-component mixed adhesive material is filled to the periphery of the inlay until the multi-component mixed adhesive material completely fills the installation area; After curing, the installation is completed.

[0007] In one embodiment, the mass ratio of the epoxy resin base glue to the curing agent is 100:30.

[0008] In one embodiment, the nano-silicon dioxide is a spherical particle with a diameter of 20-30 nm.

[0009] In one embodiment, the length of the short glass fiber filaments is 4-6 mm.

[0010] In one embodiment, the added mass fraction of the nano-silicon dioxide is 0.1% to 0.15% of the total weight of the curing agent and the epoxy resin adhesive, and the added mass fraction of the short glass fiber is 15% to 20% of the total weight of the curing agent and the epoxy resin adhesive.

[0011] In one embodiment, the epoxy resin base glue is any one of epoxy resins that can be cured at room temperature, such as EA9396, EA9309.3, etc.

[0012] In one embodiment, before curing, the holes in the inlay are sealed with polymethacrylimide foam, and after curing is completed, the foam is removed.

[0013] In one embodiment, the tapering range of the tapered installation area is 1:5 to 1:3.

[0014] In one embodiment, the multi-component mixed adhesive material is injected from the bottom of the honeycomb sandwich structure composite material matrix into the installation area by means of a syringe.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a method for improving the connection strength of a composite material inlay of a honeycomb sandwich structure. The method can improve the connection strength of the composite material inlay of the honeycomb sandwich structure. By adopting an external thread inlay, improving the installation area structure to a conical surface form and adopting a multi-component mixed bonding material method, the problem of insufficient bonding strength caused by multiple pores and multiple failures in the epoxy resin glue in the previous installation process of the inlay is solved. First, the invention adopts a multi-component mixed bonding material, and significantly improves the strength and toughness of the epoxy resin bonding material by adding nano silicon dioxide and short glass fiber yarns as reinforcements. The micro-particle size and spherical particle morphology of nano silicon dioxide help to fill the micro-pores in the epoxy resin base glue, reduce pores, and improve the density and bonding force of the material. At the same time, the addition of short glass fiber yarns provides an additional fiber reinforcement effect for the bonding material, further improving the tensile strength and shear strength of the material. In addition, the design of the external thread inlay is not only easy to install, but also increases the contact area with the bonding material through the external thread, thereby improving the bonding strength. The internal thread is used as a mounting structure to ensure that the inlay is firmly fixed in the composite matrix. This design makes the connection between the insert and the composite matrix tighter and more reliable. Importantly, the installation area is designed as a cone and optimized according to the load-bearing direction, which not only increases the load-bearing area, but also helps to better fill and distribute the bonding material during the curing process.

[0016] Furthermore, the selection of the taper range not only ensures a sufficient bonding area, but also avoids the problem of uneven distribution of bonding materials due to excessive taper.

[0017] Furthermore, the method of injecting the multi-component mixed adhesive material with a syringe helps to gradually remove the air in the installation area, ensuring that the adhesive material can fully fill the entire installation area, avoiding the generation of pores and defects. This injection method also allows the adhesive material to be more evenly distributed around the inlay, further improving the bonding strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 A schematic diagram of the method for improving the connection strength of the composite material inlay of the honeycomb sandwich structure according to the present invention after installation; Among them: 1- inlay; 2- multi-component mixed adhesive material; 3- internal thread; 4- external thread; 5- epoxy resin-based glue; 6- nano-silicon dioxide; 7- short glass fiber filaments; 8- syringe; 9- installation area. DETAILED DESCRIPTION

[0019] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0020] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0021] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0022] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0023] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0024] The present invention is further described in detail below in conjunction with the accompanying drawings: The present invention provides a method for improving the connection strength of a honeycomb sandwich structure composite material inlay, the main improvements of which are that the inlay 1, the multi-component mixed adhesive material 2, and the installation area 9 are conical surfaces dug out of the composite material matrix.

[0025] The external thread insert 1 includes an internal thread 3 for installation and an external thread 4 for increasing the bonding surface area; the multi-component mixed bonding material 2 itself is a composite material, mainly including epoxy resin base glue 5, nano-silicon dioxide 6 and short glass fiber filaments 7; a syringe 8 is used as an injection tool for the multi-component mixed bonding material 2.

[0026] Specifically, the present invention provides a method for improving the connection strength of a honeycomb sandwich structure composite material inlay, comprising the following steps: S1: Add the reinforcement to the curing agent and stir evenly, then add it to the epoxy resin base glue 5 and mix evenly to obtain a multi-component mixed adhesive material 2; wherein, in order to avoid electrochemical corrosion with the metal inlay, the reinforcement of the adhesive material is selected to be insulating nano-silicon dioxide 6 and short glass fiber filaments 7; wherein the nano-silicon dioxide 6 is a spherical particle with a diameter of 20-30nm, and the added mass fraction of the nano-silicon dioxide 6 is 0.1%-0.15% of the total weight of the curing agent and the epoxy resin base glue 5, and the length of the short glass fiber filaments 7 is 4-6mm, and the added mass fraction of the short glass fiber filaments 7 is 15%-20% of the total weight of the curing agent and the epoxy resin base glue 5. wherein the epoxy resin is any one of EA9396, EA9309.3 and other epoxy resins that can be cured at room temperature, and the mass ratio of the epoxy resin base glue 5 to the curing agent is 100:30.

[0027] S2: a conical installation area 9 is opened in the matrix of the honeycomb sandwich structure composite material, an inlay 1 processed with an internal thread 3 and an external thread 4 is fixed at the center of the installation area 9, and a multi-component mixed adhesive material 2 is filled to the periphery of the inlay 1 until the multi-component mixed adhesive material 2 completely fills the installation area 9; S3: Foam is provided in the inlay 1 and then solidified. After solidification is completed, the foam is removed to complete the installation. The internal thread 3 of the inlay 1 is used as an installation structure, and the external thread 4 is used to increase the bonding contact area to improve the bonding strength.

[0028] The shape of the inlay installation area 9 is selected to be a conical surface according to the direction of the bearing force, which can increase the area of ​​the bearing area, wherein the taper range is 1:5~1:3.

[0029] Furthermore, the multi-component mixed adhesive material 2 is injected from the bottom of the honeycomb sandwich structure composite material matrix to the installation area 9 by means of an injector 8, which helps to gradually remove the air in the installation area 9 and improve the bonding strength. Specifically, the process of S2 and S3 is that after the inlay 1 is pre-fixed in the installation area 9, the configured multi-component mixed adhesive material 2 is injected from the bottom of the composite material matrix into the installation area 9 by means of an injector 8 until the inlay 1 and the multi-component mixed adhesive material 2 completely fill the installation area 9, and the installation is completed after curing.

[0030] In a specific implementation process, in combination with the above content, this embodiment discloses a method for improving the connection strength of a composite material inlay of a honeycomb sandwich structure, so as to improve the connection strength of the composite material inlay of a honeycomb sandwich structure, which specifically includes the following steps: Step 1: Clean the debonded area of ​​the inlay 1, dig out the original bonding material, and trim the bonding area into a conical structure, and then clean it with a vacuum cleaner; Step 2: according to the bonding requirements, take appropriate amounts of epoxy resin adhesive 5 and curing agent and weigh them separately according to the instructions for use, add 0.1% to 0.15% of the total weight of the two nano-silicon dioxide particles (diameter of 20 to 30 nm) to the curing agent and stir, then add 15% to 20% of the total weight of the two short glass fiber filaments 7 (length of 4 to 6 mm) to the curing agent and stir, finally add the curing agent to the weighed epoxy resin adhesive 5, mix well, and use as a multi-component mixed bonding material 2 for standby; the epoxy resin adhesive 5 is any one of EA9396 and EA9309.3; Step 3: Use foam to fill the internal thread 3 of the inlay 1 to prevent the adhesive from penetrating into the thread during installation, and place the inlay 1 according to the installation position; Step 4: After removing the needle from the syringe 8, absorb an appropriate amount of the multi-component mixed adhesive material 2 and inject it into the installation area 9 along the circumferential direction; Step 5: Use a hot air gun to promote the curing of the adhesive material. After the curing is completed, remove the foam material inside the internal thread 3, then use a tap to clean the internal thread 3, and finally repaint the surface in the repair area to complete the installation of the inlay 1.

[0031] Furthermore, in step 3, the syringe 8 needs to be used without the needle, and its volume is 20-30 ml.

[0032] See also Figure 1 The invention relates to a honeycomb sandwich structure composite material inlay connection structure which is manufactured by the above-mentioned method for improving the connection strength of the honeycomb sandwich structure composite material inlay, comprising a conical installation area 9 opened in the matrix of the honeycomb sandwich structure composite material, an inlay 1 is arranged at the center position of the conical installation area 9, and the outside of the inlay 1 is filled with a multi-component mixed adhesive material 2.

[0033] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0034] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0035] Example 1 After more than 20 years of use, the inlay 1 of a certain type of aircraft ceiling became loose, and the original bonding area was debonded, resulting in large vibration of the fuselage fairing during flight. The repair implementation process is as follows: Step 1. Clean the debonding area of ​​the inlay 1, dig out the original bonding material, and trim the installation area 9 into a conical structure with a taper of 1:5. Use a vacuum cleaner to remove excess dust and use acetone to clean the periphery of the repair area; Step 2. According to the bonding requirements, the EA9396 epoxy resin base glue and the curing agent are weighed separately in a mass ratio of 100:30, 0.1% of the total weight of the two nano-silicon dioxide particles (20nm) are added to the curing agent for stirring, and then 20% of the total weight of the two short glass fiber strands (4mm) are added to the curing agent for stirring, and finally the curing agent is added to the weighed epoxy resin base glue 5, and fully mixed for 5 minutes, as a multi-component mixed bonding material 2 for standby use; Step 3. Use foam to fill the internal thread 3 of the inlay 1 to prevent the adhesive from penetrating into the thread during installation, and place the inlay 1 at the center of the installation area 9 and fix it; Step 4. After removing the needle from the syringe 8, absorb an appropriate amount of the multi-component mixed adhesive material 2 and inject it into the installation area 9 along the circumferential direction; Step 5: Use a hot air gun to promote the curing of the adhesive material. After the curing is completed, remove the foam material inside the internal thread 3, and then use a tap to clean the internal thread 3. Finally, repaint the surface in the repair area (installation area 9) to complete the installation of the inlay 1.

[0036] The above steps were used to complete the repair of the cockpit ceiling inlay 1. After one year of actual use, no debonding occurred again.

[0037] Example 2 During the use of a certain type of aircraft main reducer fairing, the installed inlay bushing became loose, causing the fastening force to be unable to be maintained, affecting flight safety. The repair implementation process is as follows: Step 1. Clean the debonding area, dig out the original bonding material, and trim the installation area 9 into a dumbbell-shaped double-conical structure with a taper of 1:5. Use a vacuum cleaner to suck away excess dust and use acetone to clean the periphery of the repair area; Step 2. According to the bonding requirements, weigh the EA9396 epoxy resin base glue and the curing agent in a mass ratio of 100:30, add 0.1% of the total weight of the nano-silicon dioxide particles (30nm) to the curing agent and stir, then add 20% of the total weight of the short glass fiber (6mm) to the curing agent and stir, finally add the curing agent to the weighed epoxy resin base glue 5, mix thoroughly for 5 minutes, and set aside as the multi-component mixed bonding material 2; Step 3. Use foam to fill the interior of the inlay bushing to prevent the adhesive from penetrating into the threads during installation, and fix the inlay bushing in the center of the installation area 9; Step 4. After removing the needle from the syringe 8, absorb an appropriate amount of the multi-component mixed adhesive material 2 and inject it into the installation area 9 along the circumferential direction; Step 5: Use a hot air gun to promote the curing of the adhesive material. After the curing is completed, remove the foam material inside the internal thread 3, and finally perform surface touch-up paint on the repair area (installation area 9) to complete the installation of the inlay 1.

[0038] The above steps were used to complete the repair of the main reducer fairing connecting bushing. After more than 2 years of actual use, no debonding occurred again.

[0039] Example 3 After more than 20 years of use, the inlay 1 of a certain type of aircraft ceiling became loose, and the original bonding area was debonded, resulting in large vibration of the fuselage fairing during flight. The repair implementation process is as follows: Step 1. Clean the debonding area of ​​the inlay 1, dig out the original bonding material, and trim the installation area 9 into a conical structure with a taper of 1:3. Use a vacuum cleaner to remove excess dust and use acetone to clean the periphery of the repair area; Step 2. According to the bonding requirements, the EA9396 epoxy resin base glue and the curing agent are weighed separately in a mass ratio of 100:30, 0.15% of the total weight of the two nano-silicon dioxide particles (20 nm) are added to the curing agent and stirred, and then 15% of the total weight of the two short glass fiber strands (4 mm) are added to the curing agent and stirred, and finally the curing agent is added to the weighed epoxy resin base glue 5, and fully mixed for 5 minutes, as a multi-component mixed bonding material 2 for standby use; Step 3. Use foam to fill the internal thread 3 of the inlay 1 to prevent the adhesive from penetrating into the thread during installation, and place the inlay 1 in the center of the installation area 9 and fix it; Step 4. After removing the needle from the syringe 8, absorb an appropriate amount of the multi-component mixed adhesive material 2 and inject it into the installation area 9 along the circumferential direction; Step 5: Use a hot air gun to promote the curing of the adhesive material. After the curing is completed, remove the foam material inside the internal thread 3, and then use a tap to clean the internal thread 3. Finally, repaint the surface in the repair area (installation area 9) to complete the installation of the inlay 1.

[0040] The above steps were used to complete the repair of the cockpit ceiling inlay 1. After one year of actual use, no debonding occurred again.

[0041] Verified tests have shown that, compared with previous installation methods, the method for improving the connection strength of honeycomb sandwich structure composite material inlays provided by the present invention improves the connection strength by no less than 50%, meeting the subsequent use requirements of the honeycomb sandwich structure composite material inlays.

[0042] In summary, the present invention provides a method for improving the connection strength between an inlay 1 and a honeycomb sandwich composite material matrix, and the inlay 1 repair technology includes improving the structure of the bonding area of ​​the inlay 1 and using a multi-component mixed bonding material system. In the present invention, the metal inlay 1 is connected to the composite material matrix by filling with a multi-component mixed bonding material 2; the external thread 4 of the inlay 1 in the present invention increases the bonding area with the bonding material, and the selected mixed bonding material system has nanoparticle reinforcement and short fiber bridging effects, which significantly improves the bonding strength between the inlay 1 and the composite material matrix. The method of the present invention effectively solves the problems of non-standard maintenance operations and weak bonding in the previous inlay 1 connection methods, and can significantly improve the connection strength of the honeycomb sandwich structure composite inlay 1.

[0043] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for improving the connection strength of honeycomb sandwich composite material inlays, characterized in that: The following steps are involved: The reinforcement is added to the curing agent and stirred evenly, and then added to the epoxy resin base glue (5) and mixed evenly to obtain a multi-component mixed bonding material (2); wherein the reinforcement is nano-silicon dioxide (6) and short glass fiber filaments (7); A conical installation area (9) is opened in a honeycomb sandwich structure composite material matrix, an inlay (1) processed with an internal thread (3) and an external thread (4) is placed and fixed at the center of the installation area (9), and a multi-component mixed adhesive material (2) is filled around the periphery of the inlay (1) until the multi-component mixed adhesive material (2) completely fills the installation area (9); After curing, the installation is completed.

2. The method for improving the connection strength of honeycomb sandwich composite material inlays according to claim 1, characterized in that: The nano-silicon dioxide (6) is a spherical particle with a diameter of 20-30 nm.

3. The method for improving the connection strength of honeycomb sandwich composite material inlays according to claim 1, characterized in that: The length of the short glass fiber filaments (7) is 4 to 6 mm.

4. The method for improving the connection strength of honeycomb sandwich composite material inlays according to claim 1, characterized in that: The mass ratio of the epoxy resin base glue (5) to the curing agent is 100:

30.

5. The method for improving the connection strength of honeycomb sandwich composite material inlays according to claim 1, characterized in that: The added mass fraction of the nano silicon dioxide (6) is 0.1% to 0.15% of the total weight of the curing agent and the epoxy resin base glue (5).

6. The method for improving the connection strength of honeycomb sandwich composite material inlays according to claim 1, characterized in that: The added mass fraction of the short glass fiber filaments (7) is 15% to 20% of the total weight of the curing agent and the epoxy resin base adhesive (5).

7. The method for improving the connection strength of honeycomb sandwich composite material inlays according to claim 1, characterized in that: The epoxy resin base glue (5) is any one of EA9396 and EA9309.

3.

8. The method for improving the connection strength of honeycomb sandwich composite material inlays according to claim 1, characterized in that: Before curing, foam is provided in the inlay (1), and after curing is completed, the foam is removed.

9. The method for improving the connection strength of honeycomb sandwich composite material inlays according to claim 1, characterized in that: The taper range of the tapered installation area (9) is 1:5-1:

3.

10. The method for improving the connection strength of honeycomb sandwich composite material inlays according to claim 1, characterized in that: The multi-component mixed adhesive material (2) is injected into the installation area (9) from the bottom of the honeycomb sandwich structure composite material matrix by means of an injector (8).

Citation Information

Patent Citations

  • Tooth paste

    EA010030B1

Cited By

  • Variable-angle tensile load test method for composite sandwich structure

    CN121475882A